Morphology and molecular approach reveal a new species of the genus Russula subsect. Lepidinae (Russulaceae) from India - Ghosh, Aniket; Das, Kanad; Chakraborty, Dyutiparna (Phytotaxa, 2021)
Russula baniyakundensis (subg. Russula subsect. Lepidinae), a new species originating from the temperate to subalpine regions of Uttarakhand Himalaya and related to the European R. lepida Fr. is described. The phylogenetic analyses using the internal transcribed spacer (ITS) suggest that in addition to Indian sequences of R. baniyakundensis, there are sequences from China (wrongly labelled as “Russula rosea”) that are also conspecific with R. baniyakundensis in subsect. Lepidinae. Comparison with its respective allied species and a key to the described species of subsect. Lepidinae are provided for a better understanding of its taxonomic position.